Improving supply chain practices in a luxury fashion company in the Middle East and the Near East - Martins, A.; Cardoso-Grilo, T.; Touati, H. (22nd International Symposium on Logistics (ISL 2017), 2017)
Supply chain practices have a high impact on a company’s ability to compete in the market as well as in its profitability. The positioning of its inventory and its supply chain practices determine the ability to react to changes in demand, as well as the ability to fulfil customer’s requests. Cultural characteristics as well as long term practices can influence both its efficiency and effectiveness. The purpose of this paper is to analyse supply chain practices and its impact in supply chain performance in the luxury fashion industry, which represents a market not widely studied in the supply chain management literature. Particularly, this paper aims at exploring a supply chain of luxury fashion products operating in the Middle East and the Near East while assessing the efficiency and effectiveness gains from supply chain adjustments. Data was collected using direct observation and semi-structured interviews at the office of the company for the Middle East and the Near East. Findings show that the main constraint to improve customer service is lack of visibility and long lead times, which lead retailers to frequent shortage gaming practices. Analysis and managerial recommendations lead to position decoupling points, reduce lead times and simultaneously reduce customer complaints and the bullwhip effect while improving visibility and forecasting practices.